Spectrophotometric Kinetic Determination of Ultra Trace Amounts of Vanadium(V) Based on The Oxidation of Rhodamine B by Bromate in Sulfuric Acid Medium - KEYVANFARD, MOHSEN (Asian Journal of Chemistry, 2010)
A new, simple, sensitive and selective catalytic spectrophotometric method was developed for the determination of trace amounts of V(V). The method is based on the catalytic effect of vanadium(V) on the oxidation of rhodamine B by bromate in acidic medium. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of rhodamine B at 554 nm with a fixed-time method. The decrease in the absorbance of rhodamine B is proportional to the concentration of V(V) in concentration range 0.02-20 ng/mL, with a fixed time of 0.5-2.0 min from initiation of the reaction.The limit of detection of V(V) is 0.011 ng/mL. The relative standard deviation of 2.0 and 10.0 ng/mL V(V) was 2.6 and 2.8 %, respectively. The method was applied to the determination of vanadium(V) in natural water.